RECENT MODIFICATIONS OF THE CONTRAVENTION JUDICIAL REGIME - Elena Emilia STEFAN (Challenges of the Knowledge Society)
The legislation in the contraventional law domain has recently been modified, an opportunity to analyse in the current study the main modifications brought and their impact on the public and private activity. Now it is already known that, towards the end of 2017 the prevention law was addopted and then a government decision was addopted for the establishment of the contraventions that get under the new law incidence but also the remediation plan. During 2018, other legislative modifications intervened regarding the contravention judicial regime, modifications that had impact on the ongoing activity on the level of public and private domain authorities, such as, amongst others, the modification of the payment term of the contraventional fines and many more. We will focus on these aspects in the current work, this being our primary objective. Also, a secondary objective of this work refers to the fact that, through the case study we propose, we wish to surprise, from the activity of different public authorities, the dinamic of the contraventional sanctions applicability. Therefore, the most notable study methods used in the current study are: the statistic method, the deductive and informational method. In the end, we will draw the conclusions that we have reached from our documentation over the analysed subject.